The First Prenatal Visit: An Opportunity for Improved Shared Decision-Making for New Prenatal Genetic Tests [31K]. (May 2020) - Farrell, Ruth M.; Collart, Christina; Pierce, Madelyn; Edmonds, Brownsyne Tucker; Rose, Susannah
Abstract : INTRODUCTION: Discussions about prenatal genetic screening and diagnostic testing (PGT) in early pregnancy are challenging, given the complexity of available options and time constraints of the initial prenatal visit (PNV). We examined the impact of a point-of-care shared decision-making (SDM) tool on PGT discussions during PNVs. METHODS: We conducted a cluster randomized control trials to assess PGT discussions. We analyzed transcripts from 131 PNV audio recordings. Transcriptions were coded by two independent, blinded coders who measured SDM using the OPTION scale and completed a content checklist. Variables were compared using Chi-square and Fisher exact tests. RESULTS: Discussions placed greater emphasis on Trisomy (T) 21 (85.5%) than T18 (60.3%) and T13 (54.2%) and, when addressing diagnostic testing, greater emphasis on amniocentesis than CVS (53.4% vs. 24.4%). Only 21.4% of visits addressed the chance of a false positive, which providers were more likely to discuss with primiparas ( P= .03). Providers with ⩽10 years in practice were more likely to assess patients' preferred approach to education ( P= .026) and level of involvement in decision making ( P= .011). Statistically significant higher OPTION scores were noted among NEST users compared to control for 3 of the 12 SDM items. NEST users were more likely to discuss advantages of all screening options compared to control ( P= .025). CONCLUSION: Data from this study demonstrates existing challenges in addressing the decision-making needs of pregnant patients engaging with prenatal genomic-based tests. Future educational efforts should focus not just on PGT implementation, but also on efforts to enhance SDM by educating healthcare providers.